Real‐world impact of a subsidy decision of sofosbuvir–velpatasvir for treatment of chronic hepatitis C on clinical practice and patient outcomes. Issue 1 (29th November 2022) - Tan, Chee‐Kiat; Luo, Xue‐Shi; Ong, Benjamin Shao‐Kiat; Lin, Liang; Ng, Kwong‐Hoe
Abstract: Background and Aim: Sofosbuvir–velpatasvir was recommended for subsidy to treat chronic hepatitis C in Singapore in 2018. We measured the impact of the subsidy decision on clinical practice and patient outcomes. Specifically, we looked at pre‐ and post‐subsidy changes in the utilization and prescribing pattern of chronic hepatitis C treatment and the real‐world clinical effectiveness. Method: Utilization trends and prescribing patterns were assessed using aggregated drug utilization data from public hospitals' dispensing systems and clinical data from the national electronic health record database, respectively. An audit was conducted to evaluate sustained virological response rate 12 weeks post treatment (SVR12). Results: Use of sofosbuvir–velpatasvir increased sharply since its subsidy listing and dropped subsequently, whereas the utilization of comparator drugs remained low. Prescribing rate of sofosbuvir–velpatasvir increased from 13.7% in the pre‐subsidy period to 90.2% in the post‐subsidy period; 39.1% of patients previously on pegylated interferon and ribavirin switched to sofosbuvir–velpatasvir following its subsidy listing. In the audit, 365 out of 375 patients (97.3% [95% confidence interval: 95.1–98.6%]) achieved SVR12. Conclusion: The subsidy decision led to increased accessibility to patients and intended changes in clinical practice. Sofosbuvir–velpatasvir was also clinically effective in the real world. These findings augur well for the continued eradication of chronic hepatitis C infection in Singapore. Abstract : Sofosbuvir–velpatasvir was recommended for subsidy to treat chronic hepatitis C in Singapore in 2018, following which utilization trends and prescribing patterns were assessed using aggregated drug utilization data from public hospitals' dispensing systems and clinical data from the national electronic health record database. This study reports the impact of the subsidy decision on clinical practice and the clinical effectiveness of sofosbuvir–velpatasvir in a real‐world setting. The subsidy decision led to increased accessibility to patients and intended changes in clinical practice, and sofosbuvir–velpatasvir was clinically effective in the real world, auguring well for the continued eradication of chronic hepatitis C infection in Singapore.